Nucleoside phosphonates as inhibitors of HIV - Cihlar, Tomas (Henry Stewart Talks, 2011)
Nucleoside phosphonates and their antiviral spectrum, Mechanism of action and characteristics of tenofovir, Prodrugs of nucleoside phosphonates, Clinical use and efficacy, Novel classes of nucleoside phosphonates, Summary of antiviral profiles